PENGARUH TERAPI AKUPRESUR SANYINJIAO POINT TERHADAP INTENSITAS NYERI DISMENORE PRIMER PADA MAHASISWI SEMESTER VIII PROGRAM STUDI ILMU KEPERAWATAN - Efriyanthi, Sri (Coping: Community of Publishing in Nursing; Vol 3 No 2 (2015): JURNAL EDISI MEI-AGUSTUS 2015, 2015)
Dysmenorrhea is the pain felt by women when menstruation. Dysmenorrhea is usually caused by excessive release of certain prostaglandins, namely the prostaglandin F2 alpha from uterus endometrium cells. Many treatment of dysmenorrhea that has developed in the community both pharmacological and non-pharmacological therapy. One of non-pharmacologic therapy is acupressure. Acupressure is a using of touch/contact technique to balance the energy channels in the body or Qi. Sanyinjiao Point is one of acupoint or meeting point of spleen, liver and kidney channels located in the spleen meridian. This study aims to determine the effect of Acupressure Sanyinjiao Point Therapy Against Primary Dysmenorrhea Pain Intensity VIII Semester Students In Nursing Science Education Study Program. The study was conducted during one month in Nursing Science Education Study Program, Faculty of Medicine, Udayana University. Respondents received acupressure therapy Sanyinjiao point when experiencing dysmenorrhea on the first day of menstruation. This research was Quasy Experimental by designing Pre test & Post Test with Control Group, which consisted of 2 groups. The treatment group will be given acupressure intervention of Sanyinjiao point when the first day of dysmenorrhea for 20 minutes, and the control group was recommended only took a rest while doing deep breathing. The number of samples in each group was 15 people. The data were tested for data normality using the Shapiro Wilk test and it was analyzed using parametric tests Independent T-Test. Results of Independent T-Test analysis showed significant differences in pain scale changes between the two groups with the Sig. (2-tailed) was 0.000 (P <0.05) that concluded there was an Effect of Acupressure Sanyinjiao Point Therapy Of Primary Dysmenorrhea Pain Intensity VIII Semester Students In Nursing Science Education Study Program
Keywords: Acupressure Sanyinjiao Point, dysmenorrhea Pain